Direct growth of graphene on a SiGe alloy surface by chemical vapor deposition - Moon, Ji Yun; Kim, Seung Il; Heo, Keun; Lee, Jae Hyun (Journal of Semiconductor Technology and Science, 2019)
Integration of graphene with Si-based semiconductor materials, which are core-materials in complementary metal oxide semiconductor (CMOS) technology, is desirable. To date, the synergistic effects of various graphene-semiconductor hybrid systems have been shown to overcome various physical limitations of graphene and semiconductors. However, the graphene utilized in most previous studies was synthesized over a metal catalyst and required additional transfer processes that could generate irreversible physical defects and chemical contamination. Although direct synthesis of graphene on Si or Ge has been developed, research into graphene growth using silicon-germanium (SiGe) as a catalyst remains in its infancy. This is despite expectations that this method would be highly applicable to next-generation CMOS applications. Herein, we demonstrate the direct growth of graphene on a SiGe surface using a conventional chemical vapor deposition method. Optical microscopy, electron microscopy, and Raman spectroscopy were used to confirmed that the graphene was uniformly synthesized over the entire substrate. The advantages of CMOS-compatible graphene growth and high crystallinity of the synthesized graphene will provide opportunities for novel graphene-SiGe hybrid system development and next-generation CMOS technology.
Keywords: Chemical vapor deposition methods; Complementary metal-oxide-semiconductor technologies; Direct growth; High crystallinity; Physical limitations; Silicon Germanium; Synergistic effect; System development; Chemical vapor deposition; Direct growth; Graphene; Semiconductor; SiGe alloy